Authentic Leadership Perception, Trust in the Leader, and Followers’ Emotions in Organizational Change Processes - Agote, Laida; Aramburu, Nekane; Lines, Rune (The Journal of applied behavioral science, 2016)
Despite the increasing interest in emotions at work, there is still a need for more research that focus on the antecedents of emotions in organizational change contexts. Moreover, literature on the subject considers leadership and trust to be fundamental when dealing with change processes. Taking into account both ideas, it is proposed here that authentic leadership (AL) perception can influence followers’ trust and emotions during change. To test these hypotheses, we gathered and analyzed the experience of 102 Spanish human resource managers using structural equation modeling based on partial least squares. Findings show that AL is directly and positively related to followers’ trust in the leader and the experience of positive emotions. Furthermore, we found that trust mediates the relation between AL perception and the experience of negative emotions. Based on these findings, some practical implications are proposed, such as the implementation of training initiatives in order to provide human resource managers with a better understanding of the AL concept and facilitate different actions that could be carried out by them so as to contribute to trust building.